A repositioning strategy for rural tourism in Malaysia- community’s perspective - Shaista, Falak; Lo, May-Chiun; Yeo, Alvin Wee (Elsevier Ltd., 2014)
The local community is an important stakeholder in rural tourism. However the rural tourism positioning strategies have been developed from the perspective of a single stakeholder tourist, and have overlooked at local community's perspective. It is important to include community's perspective because rural tourism cannot be successful without community support. There is lack of approach to highlight the issues hindering the active participation of communities in tourism planning and implications. The aim of this research is to develop a framework for repositioning of rural tourism, by addressing community approach rather than just a tourist industry. The proposed framework, developed on the indicators from literature, will help to explore local community's perspective on current positioning and will identify the gaps for a potential repositioning. The study will provide insights to local communities, government, policymakers and other stakeholders and help them to develop effective rural tourism strategies.